Soil contamination by lead acid battery wastes inhibits seed germination and induces morphological and physiological changes in seeds of maize (Zea mays L.) and Jatropha curcas. (2013)
High concentration of heavy metals in agricultural soils has been reported to affect plan physiological processes and seed germination. There is, therefore need to ameliorate the effect of metal toxicity on germinating seeds. Greenhouse and laboratory studies were carried out to determine the effect of mixing lead (Pb) contaminated soil with uncontaminated soil on seed germination as well as on the physiological process and morphological features of germinating seeds. Greenhouse experiment involved the mixing of lead contaminated soil with uncontaminated soil in ratios; 10:90, 25:75, 50:50, 75:25, 100:0 and 0:100 to give six soil types of 10, 25, 50, 75, 100 and 0% contamination respectively with four replications. Maize and Jathropha crops were used as test crops for the experiments. The leachates collected from the six soil types were used to carry out germination test in the laboratory. They were labelled as 0. 10, 25, 50, 75 and 100% contamination. Distilled water alone and 0% contamination were used as checks. The experiments were arranged using completely randomized design replicated three times. The results showed that the Pb concentration in this contaminated soil was very high (16,130.00 mg/kg). Though, soil mixing with contaminated soil reduced the soil Pb concentration compared to control (100% contamination). none of the mixtures could support seed germination. The laboratory experiment revealed that leachates from different soil mixtures also inhibit seed germination. There was 100% reduction in germination percentage, Water uptake by the seeds was reduced compared to control. There was shrinkage in the seeds sown in all the contaminated leachates. The nitrogen and protein contents of Jatropha seeds raised with the 100% contaminated soil were reduced compared to control (leachates from uncontaminated soil). However, there was an increase in nitrogen and protein contents of maize seeds raised with 100% lead-contaminated leachate as compared to control. High lead concentration in soils contaminated by lead acid battery wastes inhibits seed germination and induced plasmolysis.